USE OF GRAVITY MODELS IN THE DEVELOPMENT OF RECREATION AND BALNEOLOGY - Khurramov Azizbek, Abdulkhakimov Zuhrali Tursunalievich, Ibragimov Gayrat, MullabayevBaxtiyarjon Bulturbayevich, Nasrullaev Azamkhon (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article draws relevant conclusions on the widespread use of recreation and balneology in the era of globalization, the rapid development of the industry and its future. Using gravitational models will be able to accelerate the development of tourism, recreation, balneology. This model is widely used to attract vacationers to tourist-recreational-balneological facilities. Finding solutions to the problems of development of tourism and recreation in the Republic of Uzbekistan, in particular, Namangan region, is the development of appropriate scientific proposals. The results of the analysis of the attraction of vacationers to the sanatorium "Chartak" in Namangan region of the Republic of Uzbekistan were obtained through multi-factor gravitational-econometric modeling. The increase in the use of existing natural resources and the quality of services in the sanatorium will increase the number of visitors to the sanatorium by 9.8 and 11.9 units, respectively. According to the results developed during the study and the defined conditions (TIC (0.02) <1 and MAPE (2.94) <10), this model is reliable. According to these forecast criteria, the forecast accuracy is high, which means that the significance of the parameter has been determined